Information Security Evaluation of Data Centre Architecture Using COBIT 5 - Nurbojatmiko, Nurbojatmiko; Irahman, Muhammad Shidqa; Nashikha, Ainun; Ramadhan, Raihan Lail (Sinkron : jurnal dan penelitian teknik informatika, 2024)
Pusat Teknologi Informasi dan Pangkalan Data (Pustipanda) UIN Jakarta is an institution in charge of managing all information systems and data management for UIN Jakarta. However, security issues are still one of the problems faced by Pustipanda today, such as data leaks, and websites that are often problematic. This research aims to assess the level of information security at the UIN Jakarta Pustipanda data centre using the COBIT 5 framework. Information security is very important in supporting organizational operations, especially facing cyber threats in the data centre environment. The research approach included document analysis, observation, and interviews with stakeholders at Pustipanda UIN Jakarta. Identification of information security weaknesses, assessment of compliance with security standards, and design of appropriate solutions are the subject of the research. It is hoped that the results will provide a comprehensive picture of information security in the data centre as well as concrete recommendations for improvement. The results of the research include an understanding of the status of information security at Pustipanda UIN Jakarta, as well as guidelines for improving information security in accordance with COBIT 5 principles. These efforts aim to reduce risk and protect the integrity, confidentiality, and availability of data in the data centre environment